2014
DOI: 10.1155/2014/573531
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Recombinant Porcine Parvovirus Virus-Like Particles inSaccharomyces cerevisiaeand Development of Virus-Specific Monoclonal Antibodies

Abstract: Porcine parvovirus (PPV) is a widespread infectious virus that causes serious reproductive diseases of swine and death of piglets. The gene coding for the major capsid protein VP2 of PPV was amplified using viral nucleic acid extract from swine serum and inserted into yeast Saccharomyces cerevisiae expression plasmid. Recombinant PPV VP2 protein was efficiently expressed in yeast and purified using density gradient centrifugation. Electron microscopy analysis of purified PPV VP2 protein revealed the self-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Previous studies revealed that the recombinant VP2 expressed in insect, eukaryotic or prokaryotic cells formed virus-like particles (VLPs) [ 16 , 18 , 19 , 41 , 42 ]. To test whether VP2 proteins were spontaneously assembled into VLPs in K. marxianus , cell lysates of KM-PPV-VP2 was scanned by TEM, and results confirmed that VP2 proteins were assembled into VLPs with a diameter of approximately 20 nm in K. marxianus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that the recombinant VP2 expressed in insect, eukaryotic or prokaryotic cells formed virus-like particles (VLPs) [ 16 , 18 , 19 , 41 , 42 ]. To test whether VP2 proteins were spontaneously assembled into VLPs in K. marxianus , cell lysates of KM-PPV-VP2 was scanned by TEM, and results confirmed that VP2 proteins were assembled into VLPs with a diameter of approximately 20 nm in K. marxianus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Attribute to high growth rate and facile high biomass, the recombinant K. marxianus strain produced 2.5 g/L PPV VLPs after just a 48 h fermentation. As a comparison, the production level of VLPs in Pichia pastoris , E. coli , S. cerevisiae is 595.76 mg/L [ 19 ], 15 mg/L [ 35 ], and 8–9 mg/L [ 18 ] respectively. Moreover, K. marxianus has a notable advantage over other strains, such as S. cerevisiae and E. coli , on high production of VLPs that there is no additional inducement during its fermentation since glucose serves as the carbon resources to support cell growth as well as an inducer for its inulinase promoter to obtain high expression of heterologous proteins [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry data were analyzed with FlowJo (FlowJo, LLC, Ashland, Oregon, USA). As an isotype control, irrelevant MAbs of IgG1 subtype prepared in-house against porcine parvovirus (PPV) were used [42].…”
Section: Methodsmentioning
confidence: 99%
“…The MAbs 1B10 and 14D6 reactive with cellular CA XII and the non-reactive MAb 9B9 are shown. Isotype control—the in house produced MAb of the relevant isotype raised against Porcine Parvovirus [ 32 ]. Secondary antibody: Alexa Fluor 488-conjugated Goat anti-Mouse IgG (H + L) (Thermo Fisher Scientific, A–11029).…”
Section: Figurementioning
confidence: 99%